2011
DOI: 10.3109/00365513.2011.575234
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal plasma TSH – estimated upper reference intervals for diagnosis and follow up of congenital hypothyroidism

Abstract: Age- and method-dependent plasma TSH reference intervals are essential for the diagnosis and management of congenital hypothyroidism. However, accurate reference intervals for plasma TSH have not been adequately defined due to the difficulties in obtaining samples from a healthy paediatric population. To overcome the difficulties in generating such intervals we estimated method-dependent plasma TSH upper-reference intervals by determining the blood spot TSH upper-reference interval from newborn blood spot TSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…The first study by Hofman et al 2003 found DBS TSH to be approximately 40% lower than serum TSH when measured using the Abbott AxSYM instrument. 20 The study by Evans et al 2011 showed that DBS TSH is approximately 50% lower than plasma TSH measured using the same Abbott Architect assay we used in our study. 21 This difference in results may be explained by a number of factors and highlights the challenges when trying to establish a DBS reference interval for TSH.…”
Section: Discussionmentioning
confidence: 60%
“…The first study by Hofman et al 2003 found DBS TSH to be approximately 40% lower than serum TSH when measured using the Abbott AxSYM instrument. 20 The study by Evans et al 2011 showed that DBS TSH is approximately 50% lower than plasma TSH measured using the same Abbott Architect assay we used in our study. 21 This difference in results may be explained by a number of factors and highlights the challenges when trying to establish a DBS reference interval for TSH.…”
Section: Discussionmentioning
confidence: 60%
“…El estadístico usado por nosotros tiene menor probabilidad de error pues se calculó sobre una población con distribución normal (posconversión logarítmica). 26 La metodología estadística de la transformación logarítmica aplicada por nosotros no es novedad, en la bibliografía sobre intervalos de referencia es defendida y recomendada por distintos autores. Kawahara y cols.…”
Section: Figura 2 Límites De Confianza Para Tsh Sérica Según Días Deunclassified
“…Los límites de decisión separan una población, los individuos por fuera de ellos (arriba o debajo) son tratados en forma diferente y estadísticamente las curvas de respuesta relativa [curvas ROC (Receiver-operating characteristic)] y los valores predictivos son las técnicas más utilizadas. 26 Si este concepto lo aplicamos en la interpretación de la pesquisa neonatal se podría decir que los intervalos de referencia de TSH serían de gran ayuda para una evaluación apropiada de los niños en riesgo de disfunción tiroidea; es decir, aquellos que fueron positivos para el valor de corte (límite de decisión) de pesquisa neonatal. En un esfuerzo para incrementar la especificidad del programa de pesquisa, nuestro objetivo fue definir intervalos de referencia para TSH sérica en RN de entre 2 y 14 días de vida.…”
Section: Introductionunclassified
“…In recent years, more sensitive and automated methods (chemiluminescence, fluoroimmunoassay, etc.) for determining both TSH and T4 in dried blood spots have been introduced (16,17,18,19,20,21). These new methods have increased sensitivity and specificity in the detection of CH.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the development of more accurate test programs, approximately 5% of CH cases may still be missed in any screening program. The reasons could be failure of sample collection, unsatisfactory samples, misinterpretation of samples and unsatisfactory recalls, the condition being subclinical or, as is true for programs which measure only TSH, failure to detect infants with central CH (14,15,16,17). …”
Section: Introductionmentioning
confidence: 99%